Efficacy of Ceftazidime-Avibactam Salvage Therapy in Patients With Infections Caused by Klebsiella pneumoniae Carbapenemase–producing K. pneumoniae. (9th June 2018) - Tumbarello, Mario; Trecarichi, Enrico Maria; Corona, Alberto; De Rosa, Francesco Giuseppe; Bassetti, Matteo; Mussini, Cristina; Menichetti, Francesco; Viscoli, Claudio; Campoli, Caterina; Venditti, Mario; De Gasperi, Andrea; Mularoni, Alessandra; et al.
Abstract: Background: Ceftazidime-avibactam (CAZ-AVI) has been approved in Europe for the treatment of complicated intra-abdominal and urinary tract infections, as well as hospital-acquired pneumonia, and for gram-negative infections with limited treatment options. CAZ-AVI displays in vitro activity against Klebsiella pneumoniae carbapenemase (KPC) enzyme producers, but clinical trial data on its efficacy in this setting are lacking. Methods: We retrospectively reviewed 138 cases of infections caused by KPC-producing K. pneumoniae (KPC-Kp) in adults who received CAZ-AVI in compassionate-use programs in Italy. Case features and outcomes were analyzed, and survival was then specifically explored in the large subcohort whose infections were bacteremic. Results: The 138 patients started CAZ-AVI salvage therapy after a first-line treatment (median, 7 days) with other antimicrobials. CAZ-AVI was administered with at least 1 other active antibiotic in 109 (78.9%) cases. Thirty days after infection onset, 47 (34.1%) of the 138 patients had died. Thirty-day mortality among the 104 patients with bacteremic KPC-Kp infections was significantly lower than that of a matched cohort whose KPC-Kp bacteremia had been treated with drugs other than CAZ-AVI (36.5% vs 55.8%, P = .005). Multivariate analysis of the 208 cases of KPC-Kp bacteremia identified septic shock, neutropenia, Charlson comorbidity index ≥3, and recent mechanical ventilation as independent predictors of mortality, whereas receipt of CAZ-AVI was the sole independent predictor of survival. Conclusions: CAZ-AVI appears to be a promising drug for treatment of severe KPC-Kp infections, especially those involving bacteremia. Abstract : We retrospectively reviewed 138 cases of Klebsiella pneumoniae carbapenemase–producing K. pneumoniae (KPC-Kp) infections in adults who received ceftazidime-avibactam (CAZ-AVI) in compassionate-use programs in Italy. CAZ-AVI appears to be a promising drug for treatment of severe KPC-Kp infections, especially those involving bacteremia.